A modified Megazyme fructan assay for rapidly screening wheat starch synthase IIa mutation populations reveals high fructan accumulation in mature grains of triple null lines. (January 2017) - Li, Xinguo; Cavanagh, Colin; Verbyla, Klara; Thistleton, Jenny L.; Wang, Hong; Pedler, Andrew; Kooij-Liu, Peggy; Li, Zhongyi; Jobling, Stephen A.
Abstract: Cereal grains are the major source of fructan intake with potential health benefits for human. Measurement of fructan levels in cereal breeding populations is a great challenge and time-consuming. In this study, K-FRUCHK and K-FRUC kits commercialized by Megazyme International Limited (Bray, Ireland) were modified and optimized in a 96 deep well plate and a thermal block (BioShake iQ, Q.Instruments, Jena, Germany). The modified assays are able to measure up to 91 samples per day with a range of fructan concentrations (0.4–10.8% in this experiment). Of the two assays, the modified K-FRUC assay is more desirable for measuring fructan levels in cereal grains with high starch content. This assay was successfully used to screen three wheat starch synthase IIa ( SSIIa ) mutation populations with a total of 466 lines. All 21 SSIIa triple null mutants showed high fructan levels (3.1–10.8%) in wholemeal flours; while all single and double nulls were similar to wild types with ∼1% of fructans. This result indicates that lack of entire SSIIa activity changes carbon flux from starch synthesis into fructan pathway. The identified 21 triple null wheat lines may have potential use for the production of high fructan staple foods. Highlights: Two high throughput fructan assays were developed by modifying Megazyme kits. The modified K-FRUC assay is desirable for measuring fructan levels in cereal grains. Starch synthase IIa ( SSIIa ) affects fructan level in wheat grains. Wheat SSIIa triple null mutants have 3.1–10.8% of fructans in wholemeal. Fructan content in SSIIa single and double nulls is similar to that in wild types (∼1%).